ANALISIS PEMERIKSAAN KASUS PERCERAIAN KARENA KEKERASAN DALAM RUMAH TANGGA (KDRT) DI PENGADILAN AGAMA SORONG PERSPEKTIF MAQASHID SYARIAH - Ansar, Magfirah Ummul Kitaby; Umrah, St. (Muadalah : Jurnal Hukum, 2025)
This study aims to analyze the examination of divorce cases due to domestic violence in the Sorong Religious Court from the perspective of maqashid sharia. This research uses qualitative research methods with an empirical-normative approach (mixed). Data were collected through interviews with judges and analysis of court decision documents. Data triangulation techniques were used to ensure the validity of the findings. The results of this study include: (1) Court procedures and the divorce trial process in the Sorong Religious Court. (2) Examination of divorce cases due to domestic violence at the Sorong Religious Court from the perspective of Maqashid Syariah, and (3) Constraints and efforts in examining divorce cases due to domestic violence at the Sorong Religious Court.